Peran Guru PAI dalam Meningkatkan Minat Belajar Siswa Tingkat SMA - Durrotul Mumtazah; Didit Darmawan (Universitas Palangka Raya, 2026)
Educational achievement at the senior high school level relies heavily upon student engagement, where the instructor serves as a pivotal variable in the pedagogical process. The phenomenon of diminished academic interest represents a significant hurdle, necessitating a profound understanding of how educators contribute to igniting active participation. This inquiry aims to examine and map the teacher's function in fostering a passion for learning among adolescents, while simultaneously uncovering the instructional tactics employed to spark such enthusiasm. The investigation adopts a literature review method with a qualitative descriptive-analytical lens, evaluating ten research articles published between 2020 and 2025 centered on teaching roles and student motivation. Findings demonstrate that the teacher’s influence in elevating student interest is holistic and multidimensional. This encompasses social competence through empathetic interaction, professional teaching performance in instructional design and evaluation, and personal integrity as an inspirational figure. Furthermore, the mastery of pedagogical and technological elements proves essential in cultivating a conducive, distinctive, and meaningful classroom environment for every learner.